Navigating Physical Activity Promotion and Policy in the Post-COVID-19-Pandemic Era - Richards, Justin; Siefken, Katja; Pratt, Michael; Bauman, Adrian; Mejía-Grueso, Juliana; Woods, Catherine B; Wendel-Vos, Wanda; Hinckson, Erica; Salvo, Deborah; Hallal, Pedro C; Ramírez Varela, Andrea (Human Kinetics, 2024)
BACKGROUND: There is limited evidence on the priorities and opportunities associated with promoting population physical activity (PA) participation for the post-COVID-19-pandemic future. PURPOSE: This study assessed government-led PA promotion efforts before and during the COVID-19 pandemic, along with post-COVID-19-pandemic priorities and recommendations. METHODS: Two separate cross-sectional surveys conducted in 2023. Survey 1 was targeted at the Global Observatory for Physical Activity (GoPA!) Country Contacts. Survey 2 also included key international informants representing influential stakeholders in PA policy implementation. RESULTS: There were 68 respondents to Survey 1, collectively representing 61 countries. An additional 37 people, including representatives from 14 key international stakeholders responded to Survey 2. Eighty-two percent of countries had national PA policies. COVID-19 widely disrupted PA policy implementation. Less than 40% of countries integrated PA into their COVID-19 response plan and more than 75% reported policies that restricted PA participation. Although most respondents indicated that government PA priorities did not change due to the COVID-19 pandemic, one in five countries reported that cross-sectoral partnership had become more important during this period. Less than a third of postpandemic governments reported as highly engaged despite the widespread proliferation of PA policies and plans prior to the pandemic. There were variations according to country, region, and income. CONCLUSIONS: Elevating PA promotion on the public health agenda is crucial for the post-COVID-19-pandemic era. At a policy level, it is critical to focus on adequate resourcing, cross-sectoral partnerships, integrated interventions, and inequities in participation. These factors have become increasingly important in the postpandemic PA policy landscape.
Keywords: epidemiology; public health; survey research; epidemiology; public health; survey research; 4206 Public Health; 42 Health Sciences; Coronaviruses; Coronaviruses Disparities and At-Risk Populations; Prevention; Emerging Infectious Diseases; Infectious Diseases; 3.1 Primary prevention interventions to modify behaviours or promote wellbeing; 1106 Human Movement and Sports Sciences; 1117 Public Health and Health Services; 1302 Curriculum and Pedagogy; Public Health; 4201 Allied health and rehabilitation science; 4206 Public health; 4207 Sports science and exercise; Humans; COVID-19; Exercise; Cross-Sectional Studies; Health Promotion; Health Policy; SARS-CoV-2; Global Health; Surveys and Questionnaires; Pandemics; Humans; Exercise; Cross-Sectional Studies; Health Policy; Health Promotion; Pandemics; Global Health; Surveys and Questionnaires; COVID-19; SARS-CoV-2; Humans; COVID-19; Exercise; Cross-Sectional Studies; Health Promotion; Health Policy; SARS-CoV-2; Global Health; Surveys and Questionnaires; Pandemics